Some Properties of Self-Compacting Concrete with Optimum Percentages of Cement Replacement Materials (Iraqi Journal of Civil Engineering, 2023)
This paper presents and discuses some properties of self-compacting concrete SCC containing optimum contents of different types of cement replacement materials CRMs like fly ah, silica fume and limestone powder. The purpose is to evaluate the performance of SCC mixtures to choose the best one for strengthening purposes of corroded reinforcement concrete beams. In a preliminary work, the theoretical optimum contents of the above materials were specified using statistical program (Minitab) and they were verified experimentally. This verification based on checking fresh properties such as slump flow, T500, L-box and segregation resistance as well as compressive strength. The optimum contents of CRMs: 14% fly ash, 19% limestone, 18% silica fume plus fly ash and 11% silica fume were selected and studied. Compressive, tensile, and flexural strengths were examined, as well as the modulus of elasticity, water absorption and porosity (which reflect the related durability properties) were examined. Test results show that the optimum verified theoretical percentage of a combination of fly ash and silica fume, at 18% by weight of cement with a fixed water-binder ratio of 0.33 showed the best overall performance. It was deduced that this SCC mix gave the highest mechanical properties and the lowest porosity and water absorption. For example, the compressive strength increased by 36.25% as compared to SCC mix containing limestone powder. Further, the porosity and water absorption decreased by 120.8% and 164% respectively as compared to the above same SCC mix. Thus, it could be used for strengthening purpose of corroded RC beams.